Case Report: DARS Mutations Responsible for Hypomyelination With Brain Stem and Spinal Cord Involvement and Leg Spasticity - Liu, Meijun; Xiao, Wen; Yang, Fang; Wang, Xueqing; Chen, Chao; Jin, Shuoguo; Ran, Ningjing; Chen, Weiyin; Yang, Dongdong (Frontiers in Genetics, 2022)
Objective: Hypomyelination with brain stem and spinal cord involvement and leg spasticity (HBSL) is a rare form of leukodystrophy presenting with varying clinical and imaging features. We report a case of HBSL to investigate the clinical and radiological characteristics of HBSL resulting from cytoplasmic aspartyl-tRNA synthetase gene (DARS) mutations. Subjects: We report a patient of HBSL with compound heterozygous mutations in DARS1. To study the potential genetic variations of the patient, targeted next-generation sequencing, whole-exome sequencing, and Sanger sequencing were used. We reviewed the clinical and radiological features of the patient. The literature was thoroughly evaluated. Results: The patient suffered from developmental regression associated with lower limbs spasticity, developmental delay, and paralysis of the lower limbs since childhood. Decreased T1 and increased T2 signals were observed on the bilateral basal, centrum ovale, frontal lobe, parietal lobe, and ganglia in cervical cord magnetic resonance imaging (MRI). The patient had two compound heterozygous mutations (NM_001349:c.1363T > C and NM_001349:c.821C > G) in the DARS1 gene. Conclusion: Two mutations in DARS1 were found to be associated with HBSL, one of them being reported for the first time. These findings can be valuable for diagnosing and providing genetic counseling to HBSL patients in the future.